PEMAHAMAN PERAWAT TENTANG MPKP TIM DAN FAKTOR-FAKTOR YANG BERHUBUNGAN DI RSD BALUNG JEMBER - Diyan Indriyani **, Asmuji * (The Indonesian Journal of Health Science, 2016)
MPKP Tim is a professional nursing practice model that aims to improve the service which always refers to the effectiveness and efficiency in providing nursing care in the treatment room. However, from the source of the data collected by the students in 2016 showed, MPKP Tim implementation at the hospital is still below 75%, which means that relatively still does not meet the standard. The study is a correlational study using cross sectional approach. This research was conducted in inpatient hospitalization in RSD Balung on the March-May 2016. The study population was all nurses? who served in inpatient RSD Balung with a sample of 50 nurses? were taken by simple random sampling. The results showed that the average value of an understanding nurse about MPKP Tim is 8.5 points out of 16 maximum points. Based on the multiple linear regression statistical tests showed that the defenders' participation in training activities or MPKP and ward management has the closest relationship with an understanding nurses? about MPKP Tim. This research was conducted in an attempt to find an understanding nurses? about MPKP Tim and can provide solutions. Key Word: Nurses,  MPKP Tim